Communicative generalisation: Dialogical means of advancing knowledge through a case study of an 'unprecedented' disaster. (March 2020) - Cornish, Flora
In the interest of learning from a unique and devastating disaster, this paper develops a conceptualisation of generalisation as a communicative process. Growing from the author's experience of conducting and communicating an ethnographic case study of the community response to the Grenfell Tower disaster, a tower block fire which traumatised a West London community, and has been widely labelled an 'unprecedented' event, the paper considers ways of developing knowledge with wider application from this unique case. 'Communicative generalisation' is concerned with the significance of knowledge to epistemic communities rather than abstract universal truth. Four modes of communicative generalisation are explored. By elaborating the multi-perspectival nature of a case and its relation to its context, case studies may enrich readers' generalised other . Case studies may address an epistemic community by problematising a taken-for-granted situation or theory. A case study can extend the situations to which it may transfer by multiplying its audiences, and thus forcing its authors to take multiple perspectives. It can also extend its meaningfulness by multiplying speakers, facilitating expressions of diverse perspectives on the case. 'Communicative generalisation' distributes the agency of generalisation among authors, cases and audiences. This redistribution has implications for the politics and temporality of generalisation.